2004
DOI: 10.2190/4h2x-xd53-gk0j-91nq
|View full text |Cite
|
Sign up to set email alerts
|

Wounding the Messenger: The New Economy Makes Occupational Health Indicators Too Good to Be True

Abstract: The U.S. Bureau of Labor Statistics and workers' compensation insurers reported dramatic drops in rates of occupational injuries and illnesses during the 1990s. The authors argue that far-reaching changes in the 1980s and 1990s, including the rise of precarious employment, falling wages and opportunities, and the creation of a super-vulnerable population of immigrant workers, probably helped create this apparent trend by preventing employees from reporting some injuries and illnesses. Changes in the health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 51 publications
0
104
0
Order By: Relevance
“…These results also need to be seen in the context of the tendency of many workers not to report their injuries, especially if they are non-unionized, immigrants, or otherwise politically vulnerable [Azaroff et al, 2002[Azaroff et al, , 2004Brown et al, 2002;Scherzer et al, 2005]. Non-reporting of injuries may be due to language barriers, fear of retaliation, or lack of understanding of legal rights under Workers Compensation laws and OSHA standards.…”
Section: Discussionmentioning
confidence: 99%
“…These results also need to be seen in the context of the tendency of many workers not to report their injuries, especially if they are non-unionized, immigrants, or otherwise politically vulnerable [Azaroff et al, 2002[Azaroff et al, , 2004Brown et al, 2002;Scherzer et al, 2005]. Non-reporting of injuries may be due to language barriers, fear of retaliation, or lack of understanding of legal rights under Workers Compensation laws and OSHA standards.…”
Section: Discussionmentioning
confidence: 99%
“…Women [Chung et al, 2000;Lippel, 2003a], members of racialized or linguistic minorities [Herbert et al, 1999;Premji et al, 2008a] and immigrant workers [Azaroff et al, 2004;Gravel et al, 2010;Guthrie and Quinlan, 2005] have been shown to have more difficulties in accessing compensation. Studies in Canada [Ison, 1986;Lippel, 1999;Beardwood et al, 2005;Eakin, 2005;Lippel, 2007;MacEachen et al, 2007aMacEachen et al, , 2010, Australia [Roberts-Yates, 2003;Sager and James, 2005], and the United States [Lax and Manetti, 2001;Strunin and Boden, 2004] have shown that many workers' compensation claimants report feeling stigmatized by the process, blamed for being an injured worker, and shunned by the community and healthcare professionals because of their status as an injured worker.…”
Section: Discourses Underpinning Workers' Compensation Systemsmentioning
confidence: 99%
“…Yet the nature of compensation available often fails to meet the needs of those who are injured, a situation that is particularly acute for the precariously employed [Azaroff et al, 2004;Quinlan, 2004], who are both more likely to be assigned dangerous work [Johnstone et al, 2001;Quinlan et al, 2001;Smith et al, 2010], and more likely to receive a level of benefits that does not reflect the impact of the injury on their working and earning capacity [Cox and Lippel, 2008;Smith et al, 2010]. This, in turn, will influence the support these workers will receive when they are permanently disabled because of work injury, underestimation of the value of their earning capacity will then lead to an underestimation of rehabilitation requirements.…”
Section: Do Systems Apply Appropriate Measures For Promoting Return Tmentioning
confidence: 99%
“…The authors argued that factors that discourage employees and supervisors from reporting injuries and illnesses, growing difficulty in documenting the diagnosis of work-related conditions, accessing workers' compensation coverage for medical care and partial wage replacement for occupational health problems, and more broad governmental reforms have glossed over our vision of the work conditions of immigrant workers. They point out that, in some cases, political and social changes have actually targeted immigrant workers, making them even more vulnerable (48,49).…”
Section: Reporting Surveillance Health Care and Compensationmentioning
confidence: 99%